An enantiopure N,N,S scorpionate ligand derived from (+)-camphor - Godau, Tom; Platzmann, Florian; Heinemann, Frank Wilhelm; Burzlaff, Nicolai (Dalton Transactions, 2009)
Reductive S-S bond cleavage of a disulfide precursor 3 obtained from a pyridine-catalyzed Peterson-type reaction starting from camphorpyrazole 1, thionyl chloride and 2-methyl-2-(methyldithio)propionaldehyde yields 2,2′-bis(camphorpyrazol-1-yl)-2-methylpropane-2-thiol (HS prbpm, 4); the first zinc complexes bearing this ligand exhibit κ coordination of the ligand. © 2009 The Royal Society of Chemistry.

Cu(i) catalysed cyclopropanation with enantiopure scorpionate type ligands derived from (+)-camphor or (-)-menthone - Godau, Tom; Bleifuß, Sascha; Müller, Astrid; Roth, Thomas; Hoffmann, Susanne; Heinemann, Frank Wilhelm; Burzlaff, Nicolai (Dalton Transactions, 2011)
One-pot syntheses of three new enantiopure heteroscorpionate ligands derived from (+)-camphor or (-)-menthone are described. The ligands are obtained by reacting pyrazoles derived from (+)-camphor or (-)-menthone with sodium hydride and thionyl chloride. Subsequent reactions with pyridine and various aldehydes afford the tripod ligands in multi-gram amounts. Especially the menthopyrazole based ligand 6 showed encouraging ee values up to 69% in the Cu(i) catalysed enantioselective cyclopropanation of styrene with ethyl diazoacetate. © 2011 The Royal Society of Chemistry.